2016
DOI: 10.3389/fpls.2016.01744
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Effects of the Cell Cycle Regulator LGO in Arabidopsis Sepals

Abstract: Endoreduplication is a specialized cell cycle in which DNA replication occurs, but mitosis is skipped creating enlarged polyploid cells. Endoreduplication is associated with the differentiation of many specialized cell types. In the Arabidopsis thaliana sepal epidermis endoreduplicated giant cells form interspersed between smaller cells. Both the transcription factor Arabidopsis thaliana MERISTEM LAYER1 (ATML1) and the plant-specific cyclin dependent kinase inhibitor LOSS OF GIANT CELLS FROM ORGANS (LGO)/SIAME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 102 publications
(167 reference statements)
2
27
0
Order By: Relevance
“…Live imaging of Arabidopsis sepal pavement cells has shown that endoreduplicating cells grow at the same relative rate, on average, as their dividing neighbors (Tauriello et al, 2015); in essence, endoreduplicated cells are larger because they grow without being halved by division (Roeder et al, 2010). Endopolyploidy has also been linked to cell fate: nascent trichomes in which endoreduplication is blocked often lose their identity (Bramsiepe et al, 2010), and pavement cells differ in gene expression based on their level of endopolyploidy (Roeder et al, 2012;Schwarz and Roeder, 2016). Global transcription increases with endopolyploidy in tomato fruit (Solanum lycopersicum; Bourdon et al, 2012;Pirrello et al, 2018).…”
Section: Two Kinds Of Ploidy Change Occur In Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Live imaging of Arabidopsis sepal pavement cells has shown that endoreduplicating cells grow at the same relative rate, on average, as their dividing neighbors (Tauriello et al, 2015); in essence, endoreduplicated cells are larger because they grow without being halved by division (Roeder et al, 2010). Endopolyploidy has also been linked to cell fate: nascent trichomes in which endoreduplication is blocked often lose their identity (Bramsiepe et al, 2010), and pavement cells differ in gene expression based on their level of endopolyploidy (Roeder et al, 2012;Schwarz and Roeder, 2016). Global transcription increases with endopolyploidy in tomato fruit (Solanum lycopersicum; Bourdon et al, 2012;Pirrello et al, 2018).…”
Section: Two Kinds Of Ploidy Change Occur In Plantsmentioning
confidence: 99%
“…Wild-type Arabidopsis sepals have a pattern of interspersed small, medium, and large (giant) cells with corresponding ploidy 2C-32C ( Figures 2A and 2B, WT) (Roeder et al, 2010). The SIM-related cyclin-dependent kinase inhibitor LGO has been shown to affect the proportion of cells entering endocycles: Overexpression of LGO increases endoreduplication, and loss of function reduces it (Roeder et al, 2010;Schwarz and Roeder, 2016). We have previously shown that the transcription factor MERISTEM LAYER1 (ATML1) affects the proportion of endoreduplicated cells in a dosage-dependent manner;…”
Section: Altering Endopolyploidy Affects Cell Size But Not Organ Sizementioning
confidence: 99%
See 1 more Smart Citation
“…SMR1/LGO regulates endoreplication in giant cells of the sepal epidermis as well as during leaf development (Roeder et al, 2010), and SMR2 plays a role in the timing of the switch from cell division to endoreplication early in leaf development (Kumar et al, 2015), emphasizing the role of SMRs in controlling endoreplication. SMRs also have been implicated in blocking cell division in response to DNA damage or drought stress and in responses to pathogens (Wang et al, 2014;Yi et al, 2014;Hamdoun et al, 2016;Schwarz and Roeder, 2016;Dubois et al, 2018). Multiple SMRs from Arabidopsis, as well as other plants, can complement the sim trichome phenotype, in which cells divide several times instead of endoreplicating their DNA, indicating that there is an underlying functional similarity among all members of the family tested (Peres et al, 2007;Kumar et al, 2015).…”
mentioning
confidence: 99%
“…Consistent with such a role of CKIs in plant immune responses, overexpression of SMR1/LGO in the sepal epidermis results in overexpression of a suite of defense-response genes that overlap substantially with the set of genes upregulated in cpr5 mutants. 33 CPR5 appears to be an integral component of the plant nuclear pore complex, and a model for the role of KRPs and SMRs in effector triggered immunity has been proposed in which the CKIs are associated with CPR5 in the nuclear pore complex until released for effector-triggered immune signaling by a conformational change in CPR5 34 It remains to be resolved are how the role of KRPs and SMRs in the mitotic and endoreplication cell cycles, which presumably require free CKIs in the nucleoplasm, are related to this model.…”
Section: An Unexpected Link Between Ckis and Plant Pathogen Responsesmentioning
confidence: 99%